Cascading partial rupture of the Flores Thrust during the 2018 Lombok earthquake sequence, Indonesia - Salman, Rino (2020)
A series of four Mw > 6 earthquakes struck the northern region of Lombok, eastern Indonesia, in a span of three weeks from late July to mid-August 2018. The series was thought to be associated with the Flores thrust, but the exact mechanism causing the unusual earthquake series has remained elusive. Our Interferometric Synthetic Aperture Radar analysis, combined with insights from seismology, indicates that the events originated at different hypocenter depths with differing fault geometries, which may explain the cascading behavior of the events, and indicates that better imaging of active fault geometry might provide some insight into future rupture behavior on other similar thrust systems. Our static stress change calculations suggest that the earlier events in the sequence played a role in promoting the later events. In addition, the second event brought the most significant impact on a nearby volcano, by causing volumetric expansion at its shallow magma plumbing system and unclamping its magma ascent zone, which may potentially have an impact on its future eruptive activity. However, no volcanic activity has so far occurred after the earthquakes. Finally, our damage proxy maps suggest that the second event caused the greatest damage to buildings.